Dose‐dependent sensorimotor impairment in human ocular tracking after acute low‐dose alcohol administration. (17th December 2020) - Tyson, Terence L.; Feick, Nathan H.; Cravalho, Patrick F.; Flynn‐Evans, Erin E.; Stone, Leland S.
Abstract : Key points: Oculomotor behaviours are commonly used to evaluate sensorimotor disruption due to ethanol (EtOH). The current study demonstrates the dose‐dependent impairment in oculomotor and ocular behaviours across a range of ultra‐low BACs (<0.035%). Processing of target speed and direction, as well as pursuit eye movements, are significantly impaired at 0.015% BAC, suggesting impaired neural activity within brain regions associated with the visual processing of motion. Catch‐up saccades during steady visual tracking of the moving target compensate for the reduced vigour of smooth eye movements that occurs with the ingestion of low‐dose alcohol. Saccade dynamics start to become 'sluggish' at as low as 0.035% BAC. Pupillary light responses appear unaffected at BAC levels up to 0.065%. Abstract: Changes in oculomotor behaviours are often used as metrics of sensorimotor disruption due to ethanol (EtOH); however, previous studies have focused on deficits at blood‐alcohol concentrations (BACs) above about 0.04%. We investigated the dose dependence of the impairment in oculomotor and ocular behaviours caused by EtOH administration across a range of ultra‐low BACs (≤0.035%). We took repeated measures of oculomotor and ocular performance from sixteen participants, both pre‐ and post‐EtOH administration. To assess the neurological impacts across a wide range of brain areas and pathways, our protocol measured 21 largely independent performance metrics extracted from a range of behavioural responses ranging from ocular tracking of radial step‐ramp stimuli, to eccentric gaze holding, to pupillary responses evoked by light flashes. Our results show significant impairment of pursuit and visual motion processing at 0.015% BAC, reflecting degraded neural processing within extrastriate cortical pathways. However, catch‐up saccades largely compensate for the tracking displacement shortfall caused by low pursuit gain, although there still is significant residual retinal slip and thus degraded dynamic acuity. Furthermore, although saccades are more frequent, their dynamics are more sluggish (i.e. show lower peak velocities) starting at BAC levels as low as 0.035%. Small effects in eccentric gaze holding and no effect in pupillary response dynamics were observed at levels below 0.07%, showing the higher sensitivity of the pursuit response to very low levels of blood alcohol, under the conditions of our study. Key points: Oculomotor behaviours are commonly used to evaluate sensorimotor disruption due to ethanol (EtOH). The current study demonstrates the dose‐dependent impairment in oculomotor and ocular behaviours across a range of ultra‐low BACs (<0.035%). Processing of target speed and direction, as well as pursuit eye movements, are significantly impaired at 0.015% BAC, suggesting impaired neural activity within brain regions associated with the visual processing of motion. Catch‐up saccades during steady visual tracking of the moving target compensate for the reduced vigour of smooth eye movements that occurs with the ingestion of low‐dose alcohol. Saccade dynamics start to become 'sluggish' at as low as 0.035% BAC. Pupillary light responses appear unaffected at BAC levels up to 0.065%.